2022
DOI: 10.3390/cancers14030587
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Potential of Liquid Biopsy in HER2-Positive Breast Cancer Management

Abstract: Invasive breast cancer (BC) is the most common cancer in women with a slightly increasing yearly incidence. BC immunohistochemical characterisation is a crucial tool to define the intrinsic nature of each tumour and personalise BC patients’ clinical management. In this regard, the characterisation of human epidermal growth factor receptor 2 (HER2) status guides physicians to treat with therapies tailored to this membrane receptor. Standardly, a tumour solid biopsy is therefore required, which is an invasive pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 77 publications
(89 reference statements)
0
8
0
Order By: Relevance
“…However, in a recent study evaluating ERBB2 mutations using ctDNA in patients with advanced breast cancer, the frequency of ERBB2 mutations was 8.9% and this was higher in HER2-positive tumors than in HER2-negative tumors [ 26 ]. It has been suggested that ERBB2 mutations are acquired as a consequence of anti-HER2 therapy, which can easily be detected by ctDNA analysis [ 26 , 27 ]. In addition, ERBB2 mutations were associated with shorter PFS in HER2-positive patients who received trastuzumab plus chemotherapy in a metastatic setting.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a recent study evaluating ERBB2 mutations using ctDNA in patients with advanced breast cancer, the frequency of ERBB2 mutations was 8.9% and this was higher in HER2-positive tumors than in HER2-negative tumors [ 26 ]. It has been suggested that ERBB2 mutations are acquired as a consequence of anti-HER2 therapy, which can easily be detected by ctDNA analysis [ 26 , 27 ]. In addition, ERBB2 mutations were associated with shorter PFS in HER2-positive patients who received trastuzumab plus chemotherapy in a metastatic setting.…”
Section: Discussionmentioning
confidence: 99%
“…For BC diagnosis, a solid biopsy is a well-established technique in clinics that provides information about tumor histology and subtype. Nonetheless, mishaps in the detection of alternative biomarkers, insufficient tissue obtention, or incompatibility with long-term monitoring, among other limitations still exist ( 5 ). Compared with solid biopsy, LB is a more comprehensive diagnostic test that uses blood, urine ( 67 ), saliva, and other biological fluids ( 68 , 69 ).…”
Section: Liquid Biopsy In Breast Cancermentioning
confidence: 99%
“…Additionally, in LB, invasiveness and residual disease are minimized that also enables and simplifies the longitudinal monitoring of BC patients. LB potentiates obtaining the complete molecular picture of the tumor and, thus, enhances more precise clinical decisions ( 5 , 77 ). Indeed, a number of studies successfully consolidate the significance of LB in BC ( 78 81 ) and other cancers too ( 82 , 83 ).…”
Section: Liquid Biopsy In Breast Cancermentioning
confidence: 99%
See 2 more Smart Citations